Synaptic Function and Dysfunction in Lysosomal Storage Diseases - Rebiai, Rima; Givogri, Maria I.; Gowrishankar, Swetha; Cologna, Stephania M.; Alford, Simon T.; Bongarzone, Ernesto R. (Frontiers in Cellular Neuroscience, 2021)
Neurological lysosomal storage disorders (LSDs) are inherited genetic diseases characterized by lysosomal dysfunction and the accumulation of undegraded substrates mainly in glial but also in neurons cells. Often, patients with neurological manifestations present with severe damage to the nervous system and irreversible neuronal decline. Our understanding of the cellular basis leading to neuronal decline and damage to the nervous system in LSDs is still incomplete. Deficits in availability and function of synaptic proteins at nerve terminals, modifications of membrane structure, alterations in the docking and exocytosis of synaptic vesicles, along with deficits in synaptic vesicle recycling and inflammatory-mediated remodeling are among some of the identified causes for synaptic failure. The use of animal models of LSDs has enabled the study and identification of some of these mechanisms as contributors to neuronal dysfunction in LSDs. The goal of this mini-review is to discuss some of these aspects of synaptic dysfunction in LSDs.